MELAWAN AKSI TERORISME DI MEDIA SOSIAL: PENGGUNAAN TAGAR #KAMITIDAKTAKUT DI TWITER - Fahmi, Novrizal (Universitas Islam Negeri Raden Intan Lampung, 2018)
Social media can be a propaganda tool for misleading disseminators such as terrorism. Otherwise, it can also be a positive propaganda tool to counter negative efforts and actions. At the beginning of its emergence, ISIS, the world's terrorist organization today announced its founding through social media twitter. ISIS also continues to propagandise and spread threats to a number of countries through videos uploaded to YouTube and other social media. What is worrisome is that terrorist movements and networks have entered the world of education and among young people whose understanding and networking is also gained through the internet, such as blogs, websites and social media. Propaganda and counter-terrorist campaigns can also be done in social media. The use of tags (#) especially on twitter can build hot topics (trending topics). A topic can be a trend because of the integrated effort of the Internet citizen or because of an event that encourages people to talk about a particular topic like #Kami Tidak Takut (we are not afraid). Good and positive ideas through the use of tags can continue to be echoed to open discourses and discourses in society.